Bioavailability Study of Experimental Push–pull Osmotic Pump Tablet of Nifedipine in Dogs - Trung, Tran Quang; Thanh Hai, Nguyen; Van Lau, Trinh (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 40 No 1, 2024)
This study aimed to assess the bioavailability of experimental extended-release nifedipine tablets of push-pull osmotic pump type composed of a semipermeable membrane-coated bilayer core tablet containing PEO N10 and PEO 303 in drug layer and push layer, respectively on dogs. A test on dogs was performed using a two-way randomized crossover design with a single oral dose, fasting condition. Plasma samples were obtained at intervals and analyzed for nifedipine by UPLC-MS/MS after liquid-liquid extraction using glibenclamide as the internal standard. The pharmacokinetic parameters were calculated and the bioavailability of nifedipine extended-release tablets was evaluated by comparing the pharmacokinetic parameters between the prepared extended-release tablets of 30 mg NIF and the reference tablets of Adalat LA 30 mg. It was found that the prepared push-pull osmotic pump tablets of 30 mg nifedipine were equivalent in bioavailability to Adalat LA reference tablets of 30 mg nifedipine in experimental dogs according to the regulations of US-FDA and Vietnamese pharmacopeia 5 th edition. The main pharmacokinetic parameters of nifedipine test and reference tablets after a single oral administration were as follows:  C max 26.95 ± 7.82 (ng.mL -1 ) and 27.20 ± 6.99 (ng.mL -1 ), T max 12.33 ± 3.44 hours and 11.50 ± 3.33 hours, AUC 0-96 728.96 ± 328.87 (ng.h.mL -1 ) and 702.48 ± 404.48 (ng.h.mL -1 ), AUC 0-∞ , 741.05 ± 340.39 (ng.h.mL -1 ) and 710.71 ± 408.76 (ng.h.mL -1 ), MRT 21.80 ± 5.25 hours and 22.06 ± 5.20 hours, respectively. The 90% confidence intervals for the ratio of C max , AUC 0-∞ , and MRT values for the test and reference products, using logarithmically transformed data were 90.82% - 108.09%, 91.97% - 118.21%, 90.74% -107.62%, respectively. No statistically significant difference was found for the T max value.